2022
DOI: 10.1038/s41564-022-01215-8
|View full text |Cite
|
Sign up to set email alerts
|

The cell biology of archaea

Abstract: The past decade has revealed the diversity and ubiquity of archaea in nature, with a growing number of studies highlighting their importance in ecology, biotechnology, and even human health. Myriad lineages have been discovered, which expanded the phylogenetic breadth of archaea, and revealed their central role in the evolutionary origins of eukaryotes. These discoveries, coupled with advances that enable the culturing and live imaging of archaeal cells under extreme environments, have underpinned a better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 153 publications
(211 reference statements)
0
36
0
Order By: Relevance
“…Actin proteins are found in all three domains of life and are involved in a variety of cellular processes. Yet, actins appear to be poorly distributed among archaea (21, 51, 52). Curiously, despite resembling bacterial MreB (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin proteins are found in all three domains of life and are involved in a variety of cellular processes. Yet, actins appear to be poorly distributed among archaea (21, 51, 52). Curiously, despite resembling bacterial MreB (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Archaeal species also exhibit diverse morphologies, ranging from rods (20) and cocci (21) to triangular or square-shaped cells (22)(23)(24). While knowledge about archaeal cell-shape determinants is limited, the few components identified include the actin homolog crenactin in Pyrobaculum calidifontis, which is correlated with rod-shape in this species (25).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on archaeal cell division revealed interesting mechanisms for controlling this process and cell organization, and provided insights into the diversifying evolution of the division machinery of LUCA 13,14,21,[24][25][26] . However, compared to the extensive knowledge on bacterial and eukaryotic cell division, relatively little is known about this process in archaea.…”
Section: Discussionmentioning
confidence: 99%
“…In most bacteria, the FtsZ protein, a tubulin homolog, polymerizes into a dynamic ring-like structure (Z ring) at the division site to recruit other division proteins, forming the division machinery that splits the cell in two [1][2][3][4][5][6][7] . Archaea employ multiple division mechanisms, the two most common ones are centered around FtsZ or the endosomal sorting complex required for transport system (ESCRT-III system); some archaea lack both of these systems, suggesting yet to be discovered division mechanisms [8][9][10][11][12][13][14][15][16][17] . Recent studies of the Cdv system revealed that it shares structural similarities to the eukaryotic ESCRT machinery and possibly functions in a similar manner [17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Archaea usually present two ancestral copies of FtsZ that appear to have non-overlapping functions ( Liao et al, 2021 ). The cell division process in Archaea is not as well understood as in Bacteria, but there are some similarities with the bacterial machinery, for example, FtsA and SepF ( Pende et al, 2021 ; van Wolferen et al, 2022 ). Alternatively, some archaea that do not have FtsZ appear to have a cell division system based on ESCRT-III homologs ( Caspi and Dekker, 2018 ; Pulschen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%